2016
DOI: 10.15761/jts.1000154
|View full text |Cite
|
Sign up to set email alerts
|

The minimotif synthesis hypothesis for the origin of life

Abstract: Several theories for the origin of life have gained widespread acceptance, led by primordial soup, chemical evolution, metabolism first, and the RNA world. However, while new and existing theories often address a key step, there is less focus on a comprehensive abiogenic continuum leading to the last universal common ancestor. Herein, I present the “minimotif synthesis” hypothesis unifying select origin of life theories with new and revised steps. The hypothesis is based on first principles, on the concept of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 84 publications
(90 reference statements)
0
16
0
Order By: Relevance
“…This is exemplified by statements such as: ‘Many scientists believe life began with the spontaneous formation of (an RNA) replicator … . A more likely alternative for the origin of life is one in which a collection of small organic molecules multiply their numbers through catalyzed reaction cycles, driven by a flow of available free energy’ [ 12 , p. 105]; ‘Metabolism first scenarios are … gaining acceptance as both more plausible and potentially more predictive’ [ 13 , p. 13168] and ‘In contrast to the sophisticated high-fidelity nucleic acid-based inheritance, … I hypothesize a lower fidelity predecessor where a simpler, less-exact stepwise process gave rise to the first hereditary information system’ [ 14 , p. 294]. A succinct statement of this scenario, along with simulation evidence, is found in a paper entitled ‘Complex autocatalysis in simple chemistries’ [ 15 ].…”
Section: Mutually Catalytic Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…This is exemplified by statements such as: ‘Many scientists believe life began with the spontaneous formation of (an RNA) replicator … . A more likely alternative for the origin of life is one in which a collection of small organic molecules multiply their numbers through catalyzed reaction cycles, driven by a flow of available free energy’ [ 12 , p. 105]; ‘Metabolism first scenarios are … gaining acceptance as both more plausible and potentially more predictive’ [ 13 , p. 13168] and ‘In contrast to the sophisticated high-fidelity nucleic acid-based inheritance, … I hypothesize a lower fidelity predecessor where a simpler, less-exact stepwise process gave rise to the first hereditary information system’ [ 14 , p. 294]. A succinct statement of this scenario, along with simulation evidence, is found in a paper entitled ‘Complex autocatalysis in simple chemistries’ [ 15 ].…”
Section: Mutually Catalytic Networkmentioning
confidence: 99%
“…Of note, when considering the graded and ever-changing way in which evolution transpires, there is no compelling a priori reason to assume that life began with present-day life-characterizing molecules. This is echoed in the statement [ 14 , p. 293]: ‘A central concept applied so far in origin of life research is based on the premise that if synthesis of a compound under prebiotic conditions occurred, then it is feasible to have played a role in prebiotic evolution. Considering that the timescale of the above events may be more than a billion years, any system that propagates molecular and catalytic diversity … could explain abiotic synthesis of many of the molecules of life’.…”
Section: Chemical Opportunismmentioning
confidence: 99%
“…But how did the domains emerge? Several researchers have suggested that domains emerged from combinations of shorter peptides, originating in the RNA world (4,5,12,(47)(48)(49); presumably, peptides that could carry out molecular functions were favored and survived. In support of this mechanism, scholars have demonstrated that peptides with fewer than 55 amino acids can bind small ligands and even catalyze chemical reactions (50)(51)(52).…”
mentioning
confidence: 99%
“…The notion that domains evolved by combination of shorter peptides is also supported by computational studies aiming to detect motifs which are common features of proteins with similar function (49,(56)(57)(58)(59)(60)(61)(62). Some focused on proteins-nucleotides interactions: the Nucleotide Binding Database used "elementary functional loops" to identify recurring motifs in the binding of nucleotide cofactors (63), and Gherardini et al (64) identified nucleotide-binding motifs in the Hoogsteen, sugar, and Watson-Crick edges.…”
mentioning
confidence: 99%
“…Cooperative interactions among peptides and other molecules (amino acids, proteins, nucleic acids, lipids) were the driving forces at all stages of chemical evolution [ 18 ]. Nowadays, a chemical peptide synthetic biology approach facilitates theories on the creation of life, in particular in the eyes of scientists who believe that historically chemistry proceeds biology [ 19 , 20 , 21 ].…”
Section: Brief Historymentioning
confidence: 99%